Case report: An unusual presentation of acute promyelocytic leukemia in a middle aged female mimicking dengue infection. Issue 26 (26th June 2020) - Yapor, Laura; Zahid, Maleeha; Shrestha, Nikee; Walck, Randee; Schreiber, Zwi; Adrish, Muhammad
Abstract: Rationale: Acute promyelocytic leukemia (APL) is an uncommon subtype of acute myeloid leukemia (AML). M3v phenotype is a less common presentation of APL and these patients usually present with leukocytosis and abnormal promyelocytes that are characterized by sparse granulation and are less likely to have faggot cells with multiple Auer rods. Distinguishing M3v phenotype from acute febrile illness can be challenging as the diagnosis relies on examination of peripheral smear. Patient concerns: Fifty-seven-year-old female who presented after recent trip to Dominican Republic for high grade fever and gum bleeding. She was exposed to patients with Dengue fever during her stay. At presentation, patient had leukocytosis, thrombocytopenia, and urinalysis showing bacteria and white cell. She was started on treatment for urinary tract infection. Patient remained febrile and thrombocytopenia worsened. On day 2, flow cytometry of the peripheral smear showed 43% medium sized blasts. Fluorescence in situ hybridization was positive for promyelocytic leukemia/retinoic acid receptor alpha. Diagnoses: The patient was diagnosed with APL. Interventions: Patient was started on treatment with all-trans retinoic acid and arsenic trioxide along with supportive care Outcomes: Patient had a favorable clinical response and her symptoms subsided. Lessons: Flow cytometry of the peripheral smear is key to diagnosis of suspected APL. One must maintain high suspicion for this life-threatening condition as early diagnosis saves lives.